2009
DOI: 10.1080/00918360903275393
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Transgender/Transsexual Lives and Their Relationship with Transphobia

Abstract: The conceptualization of gender variant populations within studies have consisted of imposed labels and a diversity of individual identities that preclude any attempt at examining the variations found among gender variant populations, while at the same time creating artificial distinctions between groups that may not actually exist. Data were collected from 90 transgender/transsexual people using confidential, self-administered questionnaires. Factors like age of transition, being out to others, and participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 30 publications
5
97
0
5
Order By: Relevance
“…The fact that the race/ethnicity dummy variable loses its significance in Block 2 suggests that psychosocial risk factors like suicidality, sex work history, and family loss may in some way encompass risks for discrimination above and beyond what is captured by the simple dichotomous race variable. The finding of differential risks for unequal treatment by race is in line with research by Lombardi (2009) and Bradford et al (2013), who have previously indicated a connection between race/ethnicity and risks for discrimination for transgender people. Just as interesting was the finding that race/ethnicity and disability status…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The fact that the race/ethnicity dummy variable loses its significance in Block 2 suggests that psychosocial risk factors like suicidality, sex work history, and family loss may in some way encompass risks for discrimination above and beyond what is captured by the simple dichotomous race variable. The finding of differential risks for unequal treatment by race is in line with research by Lombardi (2009) and Bradford et al (2013), who have previously indicated a connection between race/ethnicity and risks for discrimination for transgender people. Just as interesting was the finding that race/ethnicity and disability status…”
Section: Discussionsupporting
confidence: 88%
“…Data from the present study suggest that, in both domestic violence and rape crisis services, transgender people's risks for unequal treatment frequently connect to other identities or risk factors that they hold, which is in line with research about discrimination affecting transgender people in other settings (Bradford et al, 2013;Lombardi, 2009). In general, those with other marginalized identities tend to experience increased risk for unequal treatment related to their transgender or gender non-conforming identity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations